2019
DOI: 10.1186/s41043-019-0166-4
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional risk screening—a cross-sectional study in a tertiary pediatric hospital

Abstract: BackgroundAll hospitalized patients should be screened for malnutrition risk. No universal method exists for pediatric patients.MethodsWe performed a cross-sectional study comparing three published malnutrition risk screening tools (PYMS, STAMP, and STRONGkids), applying them to each inpatient aged 1 month to 17 years over a period of five consecutive weekdays in Helsinki University Hospital, Finland.ResultsOf the eligible patients, 67% (n = 69) participated. We found that 6.2% of the children were acutely mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
4
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 21 publications
2
36
4
3
Order By: Relevance
“…Chourdakis et al [21] and Tuokkola et al [22] observed even lower Cohen's kappa values than the obtained in our study (0.37 and 0.309 respectively). All published studies consistently show that STAMP classifies many more patients as high risk compared to STRONGKids (Figure 2): 22% vs. 10% in the study by Chourdakis et al [21], 34.8% vs. 15.9% in Tuokkola et al [22], 44% vs. 27% in Ling et al [23], 27% vs. 4% in Moeeni et al [24], 19.7% vs. 9.9% according to expert observers in Galera-Martinez et al [20] and 12.3% vs. 2.5% in the present study. There is currently no consensus on the best method to assess nutritional status in hospitalized children and, therefore, on which gold standard should to be used to validate any NST [18,25].…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Chourdakis et al [21] and Tuokkola et al [22] observed even lower Cohen's kappa values than the obtained in our study (0.37 and 0.309 respectively). All published studies consistently show that STAMP classifies many more patients as high risk compared to STRONGKids (Figure 2): 22% vs. 10% in the study by Chourdakis et al [21], 34.8% vs. 15.9% in Tuokkola et al [22], 44% vs. 27% in Ling et al [23], 27% vs. 4% in Moeeni et al [24], 19.7% vs. 9.9% according to expert observers in Galera-Martinez et al [20] and 12.3% vs. 2.5% in the present study. There is currently no consensus on the best method to assess nutritional status in hospitalized children and, therefore, on which gold standard should to be used to validate any NST [18,25].…”
Section: Discussioncontrasting
confidence: 78%
“…Considering the categories of moderate and high risk, both STAMP and STRONGKids detected all cases of malnutrition at hospital admission, although with a very low specificity, below 50%. This specificity was lower than the value observed in a recent Finnish study by Tuokkola et al (69% for STAMP and 89% for STRONGKids, both with 100% sensitivity) [22], although quite similar to those referred in the systematic review of Huysentruyt et al [25], from studies using other indicators of malnutrition such as weight loss during admission, referral to a nutrition clinic or starting a There is currently no consensus on the best method to assess nutritional status in hospitalized children and, therefore, on which gold standard should to be used to validate any NST [18,25]. In our study we used respectively BMI and HFA Z-scores as indicators of acute and chronic malnutrition.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Penilaian skrining malnutrisi pada anak saat awal masuk rumah sakit disertai dengan pengkajian objektif penting dilakukan. Beberapa skrining malnutrisi baku yang dicoba implementasikan di rumah sakit di Finlandia menggunakan Screening Tool Risk on Nutritional Status and Growth (STRONGKids), Pediatric Yorkhill Malnutrition Score (PYMS), dan Screening Tool for the Assesment of Malnutrition in Paediatrics (STAMP) yang menghasilkan penilaian STRONGKids lebih akurat dan mendiagnosis malnutrisi akut (12) . Pada penelitian lain menggunakan STRONGKids dan Pediatric Nutrition Screening Tools (PNST) menghasilkan nilai sensitifitas dan spesifisitas STRONGKids lebih baik daripada PNST dalam menilai risiko malnutrisi pada anak di rumah sakit (13) .…”
Section: Abstrakunclassified
“…Penilaian STRONGKids berisi 4 pertanyaan yang menghasilkan penilaian risiko rendah dengan skor penilaian 0, risiko sedang dengan skor penilaian 1-3, dan risiko berat dengan skor penilaian 4-5 (17) . Hasil analisis diagnostik dari STRONGKids menunjukan nilai sensitifitas dan spesifisitas sebanyak 100% dan 89% sehingga membuat STRONGKids menjadi alat yang valid yang digunakan di RSUPN Dr. Cipto Mangunkusumo (12) . Selanjutnya penelitian yang menggunakan Screening Tool for Malnutrition in Pediatrics (STAMP) pada anak usia 2-17 tahun mendapatkan nilai sensitifitas dan spesifisitas yang cenderung tidak sesuai yaitu sebesar 86,5% dan 22,7% (1) .…”
Section: Instrumen Penilaian Malnutrisi DI Rumah Sakitunclassified